A new species, Hoya honglenae and the first report of H. acuminata and H. phuwuaensis (Apocynaceae, Asclepiadoideae) in the flora of Vietnam - Nguyen, van Canh; Averyanov, Leonid V.; Nguyen, Quoc Bao; Dang, van Son; Nguyen, van Khuong; Maisak, Tatiana V.; Truong, Ba Vuong (Phytotaxa, 2023)
Three species of the genus Hoya (Apocynaceae, Asclepiadoideae) are newly reported for the flora of Vietnam. One species, Hoya honglenae, is described and illustrated as new to science, and two species, H. acuminata and H. phuwuaensis, are reported as new national records known earlier, respectively, in Bhutan, Bangladesh, NE India, W China, Myanmar; and NE Thailand. The new species discovered in Phu Quoc Island (Kien Giang Province) morphologically is most close to H. phuwuaensis, but differs in the entire, straight leaf margin, leaves sparsely white speckled adaxially and dirty purple speckled abaxially, smaller yellow flowers, conoid, obtuse, distally up-cured outer angle of corona lobes, and much longer anther appendages. The paper provides morphological descriptions, data on habitat, phenology, distribution, estimated conservation status, taxonomic notes, a list of studied specimens, and color illustrations for all studied species. Taking into consideration our new data, the genus in Vietnam currently includes 44 species.